Computer graphics editor GSE and some of its applications in morphology - Karen, P; Krekule, I (Physiological research, 1995)
A simple, vector-based graphics editor, designed for experimental data presentation, schematics, large structured chemical formulae etc. in a modest IBM PC, MS DOS environment is described. Its applications in semi-automatic image analysis, especially in the implementation of design-based stereological methods for estimating global geometrical characteristics of studied samples and in 3D volume reconstruction from serial sections are discussed.
Keywords: Software; Computer Graphics; software; počítačové zpracování obrazu; mikropočítače; počítačová grafika; Microcomputers; Image Processing, Computer-Assisted